"Clusters" or "communities"? Analysing the spatial agglomeration of video game companies in Australia. Issue 2 (17th February 2016) - Darchen, Sébastien
Abstract : In this paper, I question whether agglomerations of video game companies in Australia function as clusters (spatially bound) or rather as communities (not spatially bound). The two case studies included in the analysis are the main agglomerations of video companies in Australia—Brisbane and Melbourne. The data have been collected through 21 semi-structured interviews performed between 2012 and 2014. The main findings are as follows: (1) the primary reason that video game companies come together is to share tacit knowledge and skilled labour; (2) these agglomerations do not have the attributes of "creative clusters"; and (3) new technologies enable experienced game developers to operate at the geographic periphery of the main agglomeration of developers. Therefore, to paint a more accurate picture of why some video game companies are successful—beyond simply positive externalities associated with co-localization—I propose the term "networked communities." This recognizes that social networks at varying scales (local, national, international) are being developed by video game firms in order to thrive and reach a global audience.